Genetic association of complement component 2 variants with chronic hepatitis B in a Korean population. (10th February 2018) - Namgoong, Suhg; Shin, Joong‐Gon; Cheong, Hyun Sub; Kim, Lyoung Hyo; Kim, Ji On; Seo, Jung Yeon; Shin, Hyoung Doo; Kim, Yoon Jun
Abstract: Background & Aims: Numerous single nucleotide polymorphisms associated with an increased risk of liver diseases, chronic hepatitis B and chronic hepatitis B‐related hepatocellular carcinoma have been identified. In this study, we scrutinized the genetic effects of C2 variants, which were conflicting in previous results, on the risk of chronic hepatitis B in a Korean population. Methods: We genotyped 22 common C2 genetic variants of 977 chronic hepatitis B cases including 302 chronic hepatitis B‐related hepatocellular carcinoma cases and 785 population controls. Statistical analysis was performed to examine the effects of genotype on the risk of chronic hepatitis B and chronic hepatitis B‐related hepatocellular carcinoma. Results: Logistic regression analyses showed that six C2 single nucleotide polymorphisms had significant associations with the risk of chronic hepatitis B and chronic hepatitis B‐related hepatocellular carcinoma among the Korean subjects. Stepwise analysis revealed that causal markers (rs9267665 and rs10947223) were identified among the C2 variants (stepwise P = 3.32 × 10 −9 and 2.04 × 10 −5 respectively). In further conditional analysis with previous chronic hepatitis B‐associated loci, these two single nucleotide polymorphisms were independently associated with the risk of chronic hepatitis B. In addition, we investigated the ability of genetic risk scores combining 12 multi‐chronic hepatitis B loci to predict the risk of chronic hepatitis B. Individuals with higher genetic risk scores showed increased risk for chronic hepatitis B. Conclusions: Our results suggested that the C2 gene might be a susceptibility locus for chronic hepatitis B in Korean populations. The cumulative genetic effects may contribute to future etiological explanations for chronic hepatitis B.